Longitudinal versus transverse hip arthroscopy portal cosmesis: a case-control trial of simultaneous bilateral cases - Babazadeh, Sina (J Hip Preserv Surg, 2019)
The direction and nature of incisions can impact the healing and appearance of a surgical scar. This can be attributed mainly due to skin tension and direction of force. The aim of this study was to identify differences in healing rates and scar esthetics between transverse and longitudinal portals used for hip arthroscopy. A total of 75 patients underwent bilateral hip arthroscopy for femoroacetabular impingement. All patients received a portal perpendicular to the long axis of the body on the left side (transverse portal) and parallel with the long axis of the body on the right side (longitudinal portal) for the standard anterolateral viewing portal. Postoperatively, patients were reviewed at 2 weeks, 6 weeks, 3 months and 6 months and the portal scars were assessed, photographed and measured. No patients were lost to follow-up. The transverse scars, although slightly longer, were found to be narrower at 6 weeks (3.8 mm versus 2.7 mm, P < 0.01), 3 months (4.3 mm versus 3.4 mm, P = 0.01) and 6 months postoperatively (6.1 mm versus 4.5 mm, P < 0.01). At 3 months (43 mm(2) versus 35 mm(2), P = 0.029) and 6 months (49 mm(2) versus 43 mm(2), P = 0.024), transverse incisions were noted to have significantly reduced total area compared with longitudinal incisions. There were no wound complications in either group. This study demonstrates that transverse portal positions for hip arthroscopy have an advantage over longitudinal portal positions in terms of total scar area and thickness up to 6 months postoperatively.